Nemški klasiki v gimnazijskih programih na Kranjskem - Samide, Irena (Ars et humanitas, 2025)
This article examines the role of German literary classics in secondary school educa-tion in Carniola in the period 1849-1918, when German language instruction, together with the classical languages, formed core humanities education. Based on an analysis of annual reports from four classical gymnasiums in Carniola (Ljubljana, Novo mesto, Kranj, and Kočevje), the study reconstructs the gymnasium literary canon and illumi-nates the role of Goethe and Schiller in shaping the cultural and ideological horizons of Slovenian gymnasium students. An analysis of scholarly essays, final examination Irena Sam Ide, Petra Kramberger / nemš KIKla SIKIvgImnaz IjSKI hProgramIhna Kranj SK em212papers, school assignments and required reading lists reveals that the Weimar classics represented not only literary models but also moral and ethical exemplars. The study confirms that knowledge of German literary classics played a crucial role in shaping the intellectual profile of students who later entered public and cultural life and helped shape Slovenian society at the turn of the twentieth century.
Keywords: German classics; gimnazije na Kranjskem; Goethe; gymnasiums in Carniola; literarni kanon; literary canon; nemška klasika; Schiller